Exploring the link between coffee consumption and hypertension risk - Umar Abdul Hamid; Kemal Akbar Suryoadji (Journal of Health and Therapy, 2024)
The relationship between coffee consumption and hypertension remains controversial, with studies reporting neutral, harmful, or protective effects. Understanding this association is particularly relevant in Indonesia, where coffee consumption is culturally prevalent, and hypertension is a leading public health concern. A 58-year-old male presented for a routine health examination and was found to have Stage 1–2 hypertension (168/83 mmHg), despite being asymptomatic with no risk factors. His daily intake included two cups of coffee. Despite initial lifestyle modifications, including sodium restriction, his blood pressure remained elevated, necessitating pharmacological therapy. A structured literature search was conducted using PubMed, ScienceDirect, and Cochrane Library databases. Two systematic reviews and meta-analyses were performed using the defined PICO criteria and the PRISMA methodology. One review reported no significant association between caffeine intake and hypertension (RR: 0.97, 95% CI: 0.90–1.05), while another found a modest inverse relationship at higher coffee consumption levels (RR: 0.97, 95% CI: 0.94–0.99). Moderate habitual coffee consumption does not appear to increase hypertension risk and may have protective cardiovascular effects.